Keanekaragaman Jenis dan Struktur Tegakan di Areal Tegakan Tinggal - Herianto Herianto (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Logging activities have an impact on changes in composition and standing structure, tree species distribution, community similarity and species diversity. This study aims to determine the diversity of structures and standing composition of logged-over forests. The results show that the composition and structure of the stands are ecologically different, which is indicated by the low type of species equality index. The types of stands at the level of seedlings, stakes, columns and trees from each location are almost all different. But there are some of the same types encountered dominating on the locations of 2005, 2010 and 2015 such as Shorea leprosula, Dipterocarpus borneensis, Shorea laevis, Litsea sp. The stand density at the 2005 block location is higher than the two sites in 2010 and 2015, while the location of 2015 is the location with the lowest stand density.